Annual Plan 1990-91 - Planning Commission (Planning Commission, 1990)
On the foreign trade front, helped by the introduction of a number of export incentives and overall trade reform measures, exports (measured in dollar terms) have been growing at about 17 per cent per year during the last four years. Last year, exports grew at an impressive rate of about 21 per cent. The commodity groups which mainly accounted for this growth are manufactured goods such as gems and jewellery, ready-made garments, cotton fabrics, chemicals and related products, leather and leather products and to a lesser extent engineering goods.
Government of India Planning Commission
Government of India Planning Commission